Ants3 toolkit: Front-end for Geant4 with interactive GUI and Python scripting - Morozov, A.; Margato, L.M.S.; Canezin, G.; Gonzalez, J. (Computer physics communications, 2026)
Ants3 is a toolkit that serves as a front-end for particle simulations in Geant4 and offers a custom simulator for optical photons. It features a fully interactive Graphical User Interface and an extensive scripting system based on general-purpose scripting languages (Python and JavaScript). Ants3 covers the entire detector simulation/optimization cycle, providing an intuitive approach for configuration of the geometry and simulation conditions, the possibility to automatically distribute workload over local and network resources, and giving a suite of versatile tools based on CERN ROOT for the analysis of the results. The intended application area is the development of new detectors and readout methods. The toolkit has been designed to be user-friendly for those with little experience in simulations and programming. Program Title: Ants3 CPC Library link to program files:https://doi.org/10.17632/x3kn2dw7bp.1 Developer's repository link:https://github.com/andrmor/ANTS3bundle Licensing provisions: GNU General Public License 3 Programming language: C++, C External routines/libraries: Geant4, CERN ROOT Nature of problem: Geant4 is currently one of the most broadly used platforms for Monte Carlo simulation of particle transfer through matter. The learning curve of Geant4 is very steep, as even most basic simulations require the definition of multiple C++ classes and overriding virtual functions. There are many users, especially at the beginning of their learning cycle, who do not deviate much from the code of the examples distributed with the toolkit. The existing Geant4 front-ends still do not provide a truly interactive graphical user interface and a scripting system based on general-purpose languages. Solution method: A new toolkit Ants3 is presented that serves as a front-end for particle simulations in Geant4 and offers a custom simulator for optical photons. Due to its fully interactive GUI and an extensive scripting system based on the general-purpose scripting languages (Python and JavaScript), Ants3 has a significantly flatter learning curve compared to Geant4 and most of the other existing front-ends. The toolkit covers the entire simulation cycle, featuring an intuitive approach for configuration of the geometry and simulation conditions, giving the possibility to automatically distribute work over available local and network resources, and offering a suite of versatile tools to conduct analysis of the results. A ready-to-use infrastructure for unsupervised detector optimization is also provided. A significant effort was dedicated to integrate a variety of tests directly accessible during the configuration process to reduce the number of iterations required to set-up a simulation. Wherever possible, alternative approaches for common scoring tasks are provided, enabling direct cross-checks.